GFRP Encasing Efficiency on Enhancement Composite Beams under Static Loading - Bahlol, Fahad M.; Al-Ahmed, Ali (Engineering, Technology & Applied Science Research, 2024)
Structural engineers are increasingly favoring pultruded Glass Fiber-Reinforced Polymer (pultruded GFRP) composite for its lightweight, corrosion resistance, and high strength properties. The utilization of the GFRP material in reinforced concrete structures is not yet well-defined due to a lack of scientific evidence. The study focuses on the structural performance of composite beams made of encased GFRP sections and rebar encased in reinforced concrete. This study highlights the structural significance of embedding GFRP sections in concrete beams composed of GFRP rebars and normal reinforced concrete. To achieve this goal, five different specimens were tested and analyzed under two points of static loading. The experimental program consisted of one reference beam, without the encased GFRP I-section, and four hybrid beams. The study involved installing two types of shear connectors on composite beams with GFRP I-sections to analyze their impact on shear capacity and slide resistance. The experimental findings revealed that encasing the composite beams with GFRP improved their load-bearing and energy dissipation capabilities. Additionally, the shear connectors enhanced the ultimate capacity and eliminated slipping failures. Therefore, there was a strong agreement on the numerical results demonstrating the significance of this work.